L’Humpur en BD : de fabuleuses frontières - Florence Plet-Nicolas (ReS Futurae, 2019)
In 2013, Soleil productions, specialized in fantasy comics, published Les Fables de l’Humpur by Pierre Bordage (scripter) and Olivier Roman (cartoonist), adapted from Bordage’s novel (1999). A former novel has been yet converted in strips by another artists (Les Guerriers du silence) ; but here, Bordage practises a new job, graphic novelist ; for this medium crosses text and drawing, involving a collective work with the drawer and the colourists. As the script writer, Bordage has many new constraints : he produces now text for picture, and also for a stiff framework : page and double page layout ; pre- formatted comic books with their own unity ; etc. So the accurate pattern of the novel, divided into « Livres » and « Chapitres », has been reshuffled ; so the initial « fabliaux » must be placed elsewhere, otherwise. Those new narrative frontiers find an echo with the corporal and geographical frontiers, in this great quest tale ‒ in return, there’s bargain, recreation, lucky find. These « impures » Fables de l’Humpur where really a genetic and generic hybridization novel : it’s especially befitting not a mere auto-adaptation, but an actual intermedial and co-operative creation.